A reconstruction strategy to synthesize mesoporous SAPO molecular sieve single crystals with high MTO catalytic activity. Issue 38 (21st April 2016) - Wang, Chan; Yang, Miao; Li, Mingrun; Xu, Shutao; Yang, Yue; Tian, Peng; Liu, Zhongmin
Abstract : A reconstruction strategy for the fast synthesis of mesoporous SAPO molecular sieve single crystals has been developed. The synthesized mesoporous SAPO-34 single crystals exhibit excellent hydrothermal stability and high catalytic activity in the MTO reaction. Abstract : Mesoporous SAPO-34 single crystals with tunable porosity and Si content have been fast synthesized within 4 hours by a reconstruction strategy, which show excellent hydrothermal stability and MTO catalytic activity. This new strategy is further proven to be applicable to prepare other mesoporous SAPO molecular sieve single crystals.